Influence of ceramic primers on microshear bond strength to zirconia - Raymundy Lago, Carlo Theodoro (2022)
This study aimed to investigate the effect of two ceramic primers on the microshear bond strength (µSBS) of yttria-stabilized zirconia (Y-TZP) to two types of self-adhesive resin cement and one BisGMA-based resin cement. Zirconia specimens were sandblasted with 27-µm aluminum oxide and composite cylinders were cemented with resin cement with or without the prior use of ceramic primers. Nine groups (n=12) were randomly distributed according to the cement (self-adhesive RelyX U200/3M ESPE, self-adhesive Maxcem Elite/Kerr, and BisGMA-based dual-cure RelyX ARC/3M ESPE) and ceramic primer (Z-Primer Plus/Bisco and Porcelain Liner M/Sun Medical Co.). After luting, the specimens were stored in distilled water at 37°C for 24 hours and then submitted to the µSBS test. The data were analyzed with two-way ANOVA followed by the Scheffe post hoc test (p<0.05). There were significant differences between RelyX U200 and other groups. There were also significant differences between the RelyX U200 group without ceramic primer and other groups without ceramic primers (p<0.05). Self-adhesive resin cement (RelyX U200 and MaxCem) presented higher microshear bond strength (6.17 and 2.32 MPa) than the conventional resin cement (RelyX ARC) when a porcelain primer was not used (0.43 MPa). When using Porcelain Liner M, the results of RelyX ARC (2.94 MPa) were equivalent to the results of self-adhesive cement (3.93 and 2.11 MPa). When using Z-Prime Plus, the results of MaxCem (5.36 MPa) were lower than those of RelyX U200 (9.59 MPa) but equivalent to those of RelyX ARC (6.07 MPa). When using the RelyX ARC, the use of both ceramic primers improved bond strength to zirconia. When using self-adhesive resin cement, Z-Prime Plus improved microshear bond strength values. It can be concluded that, after 24 hours, the highest µSBS results were obtained when using Z-Prime Plus and RelyX U200 self-adhesive cement.